Driving Audit Committee Disclosure: Legislation Versus Best Practice. Issue 1 (January 2020) - Coetzee, Philna; Erasmus, Lourens J.
Abstract: Stakeholders have no alternative than to rely on the credibility and effectiveness of governance and oversight structures within organizations, to protect their interest. This study investigates whether the expectation for expanded disclosure on audit committees has been adopted as part of organizational culture. The evolution of audit committee guidance in the King reports and prominent global reports were analyzed and compared to legislation governing all sectors within South Africa. A document analysis in the form of a structured content analysis was conducted to determine adherence to King guidance by South African organizations. Optimal scaling was applied to determine dimensions of disclosure, with respect to audit committee best practice. Finally, the level of adherence to legislation versus adherence to best practices is gauged within each dimension. Results support organizations to have generally increased disclosure on audit committees' composition and role. The study adds to the body of knowledge on voluntary disclosure of audit committee best practice, to be considered by policy makers and management, on what may strengthen the credibility and effectiveness of audit committee oversight as perceived by the stakeholder. The result also presents a foundation for further research within this area.